Numerical simulation and optimization of a solid state thermal diode based on shape-memory alloys. (15th September 2022) - Fernandes, C.R.; Silva, D.J.; Pereira, A.M.; Ventura, J.O.
Abstract: Overheating and heat dissipation are major issues in a large range of technological and industrial sectors that can be mitigated by thermal management systems, such as thermal diodes. Here, we propose an innovative thermal diode based on the actuation of a shape-memory alloy and investigate its performance using the Python package heatrapy . Two different configurations are considered: heating due to an internal or to an external heat source. The effect of using different gases was also studied. For the first configuration, the period increases with the gas thermal conductivity, while the opposite occurs for the second configuration. Moreover, by a suitable materials and atmosphere choice, it is possible to obtain an effective heat dissipation behavior. We found that the material volumetric heat capacity is particularly important for the performance. Thus, the thermal diode response to temperature changes can be faster (slower) if choosing a material with a lower (larger) volumetric heat capacity. Highlights: Proposal of a thermal diode based on shape memory alloy springs. Simulation of the cooling of an electronic component using numerical methods. Evaluation of the thermal diode performance for two operation modes. Period dependence on the energy storage term and on the thermal conductivity of the gas.